Edward Upward and the Critique of Everyday Late Life - Small, H (Ashgate Publishing, Ltd., 2013)
Rod Mengham Walking assumes a cardinal function in Upward's fiction, and it acquires the greatest proportional ... Nearly all the 'Nine Political Prose Pieces' revolve around walkingin Edward Upward and the Critique of Everyday Late Life ...